MODEL DINAMIK INTERAKSI DUA POPULASI - RUMLAWANG, FRANCIS YUNITO; SAMPELILING, TRIFENA (PATTIMURA UNIVERSITY, 2011)
A few phenomena are completely described by a single number. For example, the size of a population of rabbits can be represented using one number, but how to know the rate of population change, we should consider other quantities such as the size of predator populations and the availability of food. This research will discuss a model of the evolution from two populations in a Predator-Prey system of differential equations which one species â€œeatsâ€ another. This model has two dependent variables, where both of functions not hang up of times. A solution of this system will be show in trajectory in phase plane, after we get and know equilibrium points until this model be a balanced solution.